Evaluation of two red cell inclusion staining methods for assessing spleen function among sickle cell disease patients in North-East Nigeria. - Adama I Ladu; Ngamarju A Satumari; Aisha M Abba; Fatima A Abulfathi; Caroline Jeffery; Adekunle Adekile; Imelda Bates (Public Library of Science (PLoS), 2023)
The loss of splenic function is associated with an increased risk of infection in sickle cell disease (SCD); however, spleen function is rarely documented among SCD patients in Africa, due partly to the non-availability of sophisticated techniques such as scintigraphy. Methods of assessing splenic function which may be achievable in resource-poor settings include counting red blood cells (RBC) containing Howell Jolly Bodies (HJB) and RBC containing silver-staining (argyrophilic) inclusions (AI) using a light microscope. We evaluated the presence of HJB-and AI-containing RBC as markers of splenic dysfunction among SCD patients in Nigeria. We prospectively enrolled children and adults with SCD in steady state attending outpatient clinics at a tertiary hospital in North-East Nigeria. The percentages of HJB-and AI-containing red cells were estimated from peripheral blood smears and compared to normal controls. There were 182 SCD patients and 102 healthy controls. Both AI- and HJB-containing red cells could be easily identified in the participants blood smears. SCD patients had a significantly higher proportion of red cells containing HJB (1.5%; IQR 0.7%-3.1%) compared to controls (0.3%; IQR 0.1%-0.5%) (P <0.0001). The AI red cell counts were also higher among the SCD patients (47.4%; IQR 34.5%-66.0%) than the control group (7.1%; IQR 5.1%-8.7%) (P < 0.0001). The intra-observer reliability for assessment of HJB- (r = 0.92; r2 = 0.86) and AI- containing red cells (r = 0.90; r2 = 0.82) was high. The estimated intra-observer agreement was better with the HJB count method (95% limits of agreement, -4.5% to 4.3%; P = 0.579).We have demonstrated the utility of light microscopy in the assessment of red cells containing-HJB and AI inclusions as indices of splenic dysfunction in Nigerian SCD patients. These methods can be easily applied in the routine evaluation and care of patients with SCD to identify those at high risk of infection and initiate appropriate preventive measures.